Assessing the relationships between property rights and technology adoption in smallholder agriculture: a review of issues and empirical methods - Place, Frank; Swallow, Brent M. (International Food Policy Research Institute, 2000)
Studies of the relationships between property rights and technology adoption are complicated in several respects. First, there are challenges involved in defining and measuring property rights and tenure security. Second, there are several different valid purposes for undertaking such studies and each purpose may require a different approach. Third, there are a number of difficult theoretical and empirical issues involved in such studies, particularly in defining technology, identifying key dimensions of property rights, and accounting for the endogeneous determination of property rights